Deskripsi Kualitas Butir Soal Ulangan Akhir Semester Tahun Ajaran 2019/2020 Mata Pelajaran Kimia SMA Negeri 1 Wakorumba Selatan - Alfian Gunardi; Rustam Musta; La Harimu (Jurusan Pendidikan Kimia FKIP Universitas Halu Oleo, Jl. HEA. Mokodompit Kampus Hijau Bumi Tridharma Andounohu Kendari, Gedung MIPA FKIP UHO Sulawesi Tenggara – Indonesia, 2022)
Research Description of the Quality of the Final Semester Exam Questions for the 2019/2020 Academic Year for Chemistry Subjects at SMA Negeri 1 Wakorumba Selatan. This research was conducted to determine the validity, reliability, level of difficulty, discriminatory power, standard error of measurement, distribution of questions based on language subjects and learning indicators, and level of difficulty based on Bloom's taxonomy, in the odd semester class X chemistry subjects. The object of research includes all items and a list of grade X students of SMA Negeri 1 Wakorumba Selatan who have taken the 2019/2020 end of the odd semester test with a total of 78 students. The data collected by the documentation technique that will be analyzed are (1) the 2019/2020 Odd Semester Final Test Questions, the validity of the items is 100% valid with 0.1876 > 0.8843; (2) The reliability coefficient is in the range of r11 = 0.90 r < 1.00 (3) The level of difficulty is in the range of 0.58 – 1.00 which is classified as moderate; (4) 0.43 < DB 0.62 ie 4 items and 3 items between 0.32 < DB 0.40 (enough); (5) The results of the measurement standard error with a value of 0.98, thus all items have moderate or sufficient quality; (6) The distribution of questions contains 3 questions that are not appropriate in the subject matter and learning indicators in the RPP Class X Chemistry subject for the 2019/2020 Academic Year of SMA Negeri 1 Wakorumba Selatan; and (7) The difficulty level based on bloom's taxonomy consists of C1=20%, C2=15%, and C3=15%.